2008
DOI: 10.1080/00071660802094156
|View full text |Cite
|
Sign up to set email alerts
|

Survey of chicken rearing conditions in Italy: effects of litter quality and stocking density on productivity, foot dermatitis and carcase injuries

Abstract: 1. A survey was carried out to assess some welfare indicators in broilers reared by the largest poultry companies in Italy, to determine whether they accord with European proposal COM (2005) 221 final. 2. Productive traits, carcase injuries and foot dermatitis were recorded from 279,640 broiler chickens reared in winter and in summer in 5 farms representative of the Italian production system. 3. The densities currently used in Italy are in accordance with the European proposal, which recommends that broilers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 26 publications
4
71
1
5
Order By: Relevance
“…Previous studies (Al Homidan et al 1997;Meluzzi et al 2008) have shown reduced NH 3 emissions in response to increased litter depth with or without a change in stocking density, although this effect was not found by Elwinger and Svensson (1996). Considering the lack of response in ammonia emissions, and the elevated N 2 O in the present study, this approach was ineffective for mitigating GHG.…”
Section: Mitigation Of Gaseous Emissionscontrasting
confidence: 46%
See 1 more Smart Citation
“…Previous studies (Al Homidan et al 1997;Meluzzi et al 2008) have shown reduced NH 3 emissions in response to increased litter depth with or without a change in stocking density, although this effect was not found by Elwinger and Svensson (1996). Considering the lack of response in ammonia emissions, and the elevated N 2 O in the present study, this approach was ineffective for mitigating GHG.…”
Section: Mitigation Of Gaseous Emissionscontrasting
confidence: 46%
“…Mitigation focussed on litter management by increasing the litter depth has shown reduced NH 3 emissions (Al Homidan et al 1997). Meluzzi et al (2008) found that increased litter and reduced stocking density corresponded to lower moisture content, N content and NH 3 emissions. However, the impact of changed litter depth or dietary CP on GHGs is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In intensive commercial production the use of ventilation along with the adoption of curtains to increase the air speed has spread due to the beneficial effects on bird welfare in relation to the heat dissipation. The effect of stocking density on feed conversion rate is controversial since some authors found that this trait improved or worsened at high stocking densities whereas others did not observe any effect (Shanawany, 1988;Bessei, 1993;Meluzzi et al, 2008). Shanawany (1988) reported an increased mortality rate as stocking density increased.…”
Section: Stocking Densitymentioning
confidence: 99%
“…a broiler production shed) by a 'heat wave' or long-term increase in maximum temperature exceed the ventilation capacity, then, in addition to potential heat stress on the birds, other variables will be affected. Water usage by the stressed birds will increase (May and Lott, 1992;Belay and Teeter, 1993), litter quality may deteriorate, this will result in increased incidence of pathology and losses (Bessai, 2006;Manning et al, 2007;Meluzzi et al, 2008;Alain et al, 2009;Kyvsgaard et al, 2013) and the final wet litter will present problems of emissions and disposal (Topper et al, 2008;Singh et al, 2009). Obviously, during animal transport (catching/handling/ loading/in transit) and the associated procedures, similar factors will determine the on-board environment for the animals and their effects.…”
Section: Thermal Stress -Impacts and Adaptationsmentioning
confidence: 99%